Incontro Fuori Luogo. Interview with Elisabetta Camussi - Marotta, Ilaria (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
In this issue, for “Incontri Fuori Luogo” we interviewed Elisabetta Camussi, professor of Social Psychology at the University of Milan Bicocca, appointed by the Prime Minister Giuseppe Conte - in April 2020 - member of the Committee of economic experts - social for the task force led by Vittorio Colao.